(untitled) (The Review of Diabetic Studies, 2024)
Background: The diagnostic odyssey for patients with rare and complex diseases—characterized by protracted, costly, and often inconclusive testing—represents a significant failure of traditional, siloed diagnostic paradigms. The integration of multi-omics data (genomics, transcriptomics, proteomics, metabolomics) within the clinical laboratory promises a paradigm shift from sequential analysis to a holistic, systems biology-based diagnostic model. The successful translation of this approach hinges on its integration across the broader healthcare ecosystem, including radiology, health administration, and nursing. Aim: This narrative review aims to synthesize current evidence on the convergence of multi-omics platforms within the advanced medical laboratory and to articulate its essential interdependencies with key clinical and operational domains to enable a system-wide transformation in rare disease diagnosis. Methods: An integrative narrative review methodology was employed. A systematic search of PubMed, Scopus, and Web of Science was conducted for literature published between 2010 and 2024, using terms related to multi-omics, rare diseases, diagnostics, and interdisciplinary care. Results: Multi-omics integration demonstrably increases diagnostic yield in rare diseases by 10-40% over exome sequencing alone. Its clinical impact is maximized when tightly coupled with quantitative imaging phenotypes from radiology, supported by strategic health administration frameworks for resource allocation and reimbursement, and operationalized by informatics-savvy nursing teams for precision patient management and longitudinal data collection. Conclusion: Integrated multi-omics represents the vanguard of precision diagnostics, offering a powerful path to end diagnostic uncertainty. Its translation into routine practice necessitates not only new laboratory competencies and bioinformatic standards but also a deliberate, collaborative redesign of workflows with radiology, health administration, and nursing. The future diagnostic paradigm requires the medical laboratory to evolve from a provider of discrete results into the core of a multidisciplinary, data-integrated care team.